GERAKAN sosial islam : teori, pendekatan dan studi kasus / Janine A. Clark...[et.al]; editor, Quintan Wiktorowicz - CLARK, Janine A.; WIKTOROWICZ, Quintan (Gading Publishing, 2012)
viii, 564 hlm. ; 21 cm.